Financial perceptions and subjective well-being among older adults - Jafari Bidgoli, Maryam; Gregg, Abbey; Stager, Catanya G.; Crowther, Martha (Frontiers in Psychology, 2026)
ObjectiveTo examine how subjective financial well-being (SFWB) relates to subjective well-being (SWB) among older adults in the U.S. Beyond material resources, SFWB reflects perceptions of present and future security, stability, and freedom of choice. This study tested whether hopelessness mediates the SFWB–SWB relationship and whether perceived social support, both positive (PSS) and negative (NSS), moderates this pathway.MethodsData came from 4,570 respondents (Mean age = 69; 56% female) in the Health and Retirement Study, a nationally representative panel survey of U.S. adults over age 50, sponsored by the National Institute on Aging. SFWB was measured using the Consumer Financial Protection Bureau’s (CFPB) 10-item scale, a multidimensional instrument that captures not only current financial security but also expectations for future financial stability and control. SWB was measured using Diener’s Satisfaction With Life Scale. Hopelessness was assessed with a 4-item index, and perceived social support was measured across four relational domains (spouse, children, family, friends), using 28 items divided into PSS and NSS. Analyses were conducted using PROCESS (v5.0) in SPSS, controlling for sociodemographic factors.ResultsSFWB was positively associated with SWB and negatively associated with hopelessness. Hopelessness significantly mediated the SFWB–SWB link, accounting for 24.4% of the total effect. NSS significantly moderated the SFWB–hopelessness pathway, amplifying the indirect effect of low SFWB on SWB. PSS had a weaker but still significant moderating effect. When both forms of support were modeled simultaneously, only NSS remained a significant moderator.ConclusionSFWB significantly contributes to older adults’ life satisfaction, partly by reducing hopelessness. This multidimensional measure is important in aging research because it reflects not just income or assets but also perceived financial security, stability, and the freedom to make choices in the present and future. Negative social support intensifies the psychological toll of financial insecurity, while positive support provides limited buffering. Interventions should address both financial perceptions and social relationships to strengthen resilience and well-being in later life.